Electrical machines - Bhattacharya, S. K. (McGraw Hill Education (India) Private Limited, 2014)
In this edition of Electrical Machines, as in the previous ones, the author begins with a generalized approach of explaining the principles of all electrical machines, and then builds on those principles to deal with individual machines.